A conceptual framework for designing and building Web-based Revenue-sharing Collaboration Systems (WRCS) in supply chain management. (6th January 2009) - Tu, Yanbin; Lu, Min
Good collaboration plays an important role in effective supply chain management. The main obstacle to collaboration within a supply chain is the conflict between each enterprise's local optimisation and the chain's global optimisation. We show that with relationships, trust, contracts and other social factors, the sharing and reallocation of revenue can be used to align with the objectives of each member of the supply chain management, from local to global optimisation. We propose a Web-based Revenue-sharing Collaboration System (WRCS) that takes advantage of Information Technology (IT) in the digital economy. We outline the WRCS scheme, which includes four components: 1) measuring performance, 2) monitoring performance and revenue reallocation, 3) Global Optimisation Algorithm (GOA), 4) reconfiguration (planning, forecasting and recommendation). We identify the technology and system requirements for WRCS and illustrate the difference between Collaborative Planning, Forecasting and Replenishment (CPFR) systems and WRCS. The challenges, impediments and enablers for the implementation of the proposed collaboration system are also discussed.